Current therapies and new developments in NASH. Issue 10 (16th June 2022) - Dufour, Jean-François; Anstee, Quentin M; Bugianesi, Elisabetta; Harrison, Stephen; Loomba, Rohit; Paradis, Valerie; Tilg, Herbert; Wong, Vincent Wai-Sun; Zelber-sagi, Shira
Abstract : Non-alcoholic steatohepatitis is becoming the most important aetiology for advanced liver disease. There has been important progress in the field in recent years and the complexity of the pathophysiology of NASH is better understood. Multiple non-invasive circulating and imaging biomarkers have been tested. The importance of lifestyle has been recognised and several drugs are being tested in clinical trials. This review addresses the challenges that healthcare professionals face in the management of NASH patients.